PEMANFAATAN DATA MINING CLUSTERING DALAM PENENTUAN MEDIA PROMOSI UMKM DI KOTA BATAM - tan, Fitrini; ELISA, ERLIN (LPPM Universitas Putera Batam, 2021)
The more advanced technology, many things can be done by society. The most widely accessed today is social media. At this time, many UMKM are starting to promote their business on social media. However, with so many kinds of social media, UMKM have difficulty in determining which social media is the most frequently accessed by the public. So, in this final project, the writer is interested in researching the most demanded promotional media by using one of the methods from data mining technique specifically algorithm clustering K-means method. Algorithm clustering K-means can help the writer to group the promotional media that is most demanded by people in Batam City especially those in Batam Kota district based on respondent data from distributing questionnaires that have been done by the writer. There will be 3 categories in the final result that are the most demanded, less demanded and least demanded. And to get these result, manual calculations will be done by clustering K-means method and verification using Rapidminer 5.3 software.